(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This essay argues on the need to focus on state history—in this case, Pahang state history—as a way of enhancing the national history. As a starting point, a review of the existing literature highlights gaps which require attention in the writing of such history for Pahang. The review starts with the traditional texts relating to Pahang history followed by the major works that have been written thus far: the 1891–1895 anti-British uprising; the Orang Asli in state history; migration; change before 1957; the post-1957 in Pahang history; museums and state history; and gaps in both the visual and printed narratives on Pahang history. The discussion is based on secondary works on Pahang published in both Malay and English.